The future of dementia research: assessments in mid-life. (2nd January 2019) - Palmer, Sarah
Abstract : A number of studies have been carried out recently trying to establish a link between dementia and other health conditions in earlier life. Sarah Palmer discusses two of these studies, which set out to make easier assessing the likelihood of cognitive decline.